Plasma DNA integrity as a biomarker for primary and metastatic breast cancer and potential marker for early diagnosis - Madhavan, Dharanija; Wallwiener, Markus; Zucknick, Manuela; Nees, Juliane; Schott, Sarah; Cuk, Katarina; Trumpp, Andreas; Sohn, Christof; Schneeweiss, Andreas; Surowy, Harald; Burwinkel, Barbara (Breast cancer research and treatment, 2014)
Circulating or cell-free DNA (cfDNA) has been evaluated as a biomarker in many cancers including breast cancer. In particular, integrity of cfDNA has been shown to be altered in cancers. We have estimated the biomarker potential of cfDNA in primary (PBC) and metastatic breast cancer (MBC). cfDNA integrity (cfDI) and concentration were determined in plasma of 383 individuals, including 82 PBC and 201 MBC cases, as well as 100 healthy controls, by measuring ALU and LINE1 repetitive DNA elements using quantitative PCR. The MBC patient group was further sub-divided into patients with detectable circulating tumour cells (CTCpos-MBC, n = 100) and those without (CTCneg-MBC, n = 101). A hierarchical decrease in cfDI and increase in cfDNA concentration from healthy controls to PBC and further onto MBC patients were observed. Investigation of cfDNA in media of cell lines was in concordance with these results. Combination of cfDI and cfDNA concentration could differentiate PBC cases from controls (area under the curve, AUC = 0.75), MBC cases from controls (AUC = 0.81 for CTCneg-MBC, AUC = 0.93 for CTCpos-MBC), and CTCneg-MBC from CTCpos-MBC cases (AUC = 0.83). cfDI additionally demonstrated a positive correlation to progression-free (HR of 0.46 for ALU, P = 0.0025) and overall survival (HR of 0.15 for ALU and 0.20 for LINE1, P < 0.0001) in MBC, and had lower prediction error than CTC status. Our findings show that reduced cfDI and increased cfDNA concentration can serve as diagnostic markers for PBC and MBC, and cfDI as a prognostic marker for MBC, thereby making them attractive candidates for blood-based multi-marker assays.